Quantifying the relevance and stage of disease with the Tau image technique. - Merla, A.
Discusses a complementary diagnostic imaging technique based on infrared functional imaging. It is concluded that the Tau images obtained with our method provide a large amount of information. The method, in fact, correctly depicts the ill and symptomatic situation; moreover, it is able to identify the surface projection onto the skin of the damaged areas and, by means of the evaluated value of the Tau time, the stage of the disease. Additionally, it is possible to evaluate the evolution of the clinical situation following a rehabilitation therapy and to quantitatively compare the different Tau images recorded at different times.
Keywords: Tau time; Clinical situation; Complementary diagnostic imaging technique; Disease stage; Infrared functional imaging; Medical diagnostic imaging; Rehabilitation therapy; Surface projection identification; Symptomatic situation; Tau image technique